Integration of Green Skills in Technology and Vocational Education Curricula: Challenges and Opportunities for SMK Graduates Toward the Green Economy Era: Integrasi Green Skills dalam Kurikulum Pendidikan Teknologi dan Kejuruan: Tantangan dan Peluang bagi Lulusan SMK Menuju Era Ekonomi Hijau - Rizky Aditya Pratama; Putri Indah Lestari; Muhammad Fajar Ramadhan (PT. Berkah Smart Academica, 2026)
ABSTRACT The transition toward a green economy demands a significant transformation of competencies within the vocational education sector to produce an environmentally conscious workforce. This study analyzes the integration of green skills into Indonesia's Vocational High School (SMK) curriculum while identifying structural barriers and labor market opportunities. Employing a systematic literature review (SLR) for the 2015-2025 period using the Synthesis Without Meta-analysis (SWiM) framework, the study synthesized 42 peer-reviewed articles and 5 national policy documents (RPJMN and Bappenas Green Roadmap). The results reveal a distinct competency maturity gap between teachers (scores 2.24-2.91) and students (scores 2.18-2.59) based on harmonized metrics from secondary data. Student scores remain in the low category primarily due to limited school facilities and a lack of direct exposure to green industry standards. Key integration barriers include a curriculum lacking explicit green indicators and low teacher pedagogical readiness. Conversely, labor absorption opportunities are substantial, with a projected need for 1.8 million green workers by 2030 in the renewable energy and waste management sectors, as targeted in the national green workforce roadmap. Managerial solutions suggest curriculum synchronization with circular industry standards. This research recommends that Kemendikdasmen and Bappenas strengthen Project-Based Learning (PjBL) models and Triple Helix collaboration to align vocational education with national low-carbon transformation strategies ABSTRAKTransisi menuju ekonomi hijau menuntut transformasi kompetensi yang signifikan di sektor pendidikan vokasi untuk menghasilkan tenaga kerja yang sadar lingkungan. Penelitian ini menganalisis integrasi green skills (keterampilan hijau) dalam kurikulum Sekolah Menengah Kejuruan (SMK) di Indonesia, mengidentifikasi hambatan struktural, serta memetakan peluang pasar kerja. Menggunakan pendekatan tinjauan literatur sistematis (SLR) periode 2015-2025 dengan kerangka kerja Synthesis Without Meta-analysis (SWiM), studi ini menyintesis 42 artikel jurnal dan 5 dokumen kebijakan nasional (RPJMN dan Peta Jalan Bappenas). Temuan menunjukkan adanya kesenjangan kematangan kompetensi antara guru (skor 2,24-2,91) dan siswa (skor 2,18-2,59) berdasarkan harmonisasi metrik data sekunder. Skor siswa berada pada kategori rendah yang dipicu oleh keterbatasan sarana sekolah dan minimnya paparan industri hijau. Hambatan utama mencakup kurikulum yang belum memuat indikator hijau secara eksplisit serta kesiapan pedagogis guru yang rendah. Di sisi lain, terdapat peluang penyerapan 1,8 juta tenaga kerja hijau pada tahun 2030 di sektor energi terbarukan dan pengelolaan limbah sesuai target peta jalan tenaga kerja hijau nasional. Solusi manajerial yang diusulkan adalah sinkronisasi kurikulum dengan standar industri sirkular. Penelitian ini merekomendasikan agar Kemendikdasmen dan Bappenas memperkuat model pembelajaran berbasis proyek (PjBL) dan kolaborasi Triple Helix untuk menyelaraskan pendidikan vokasi dengan strategi transformasi ekonomi rendah karbon nasional